PEMODELAN PEMBANGKIT LISTRIK FOTOVOLTAIK YANG TERHUBUNG KE JARINGAN - Agus Yogianto; Ibnu Hajar; Septianissa Azzahra (KILAT, 2018)
PLTS performances as a power plant does not only convert energy, so that electricity is generated, but in the study of power systems it becomes a major element that has an important role in the study of power systems. As a power system element, the PLTS acts as an element of electricity generation in this study modeled as a PV system and connected to the network, so it must meet the requirements of the electric power network operation. Through MATHLAB / SIMULINK modeling and simulation, a 100 kW peak PLTS power plant has been modeled connected to the network. From the simulation and analysis obtained, this PLTS model shows that the connected load affects the voltage condition but does not affect the frequency. The load power factor also affects the network, namely with a lower load power factor, it affects the voltage on the network.